PERANCANGAN POLA PENGECORAN CLAMPING CONNECTOR UNTUK LISTRIK TEGANGAN TINGGI - Pradana, Angga Reyvaldi (ELEMEN : JURNAL TEKNIK MESIN, 2024)
The development of casting patterns for clamping connectors in high-voltage electrical applications is the focus of this research. It aims to design products and patterns, produce prototypes, and test the casting process using sand casting techniques. The research methods include a literature review, CAD design, CNC prototype creation, and casting evaluation. Results show that the designed patterns were successfully implemented in the casting process. Tests indicate that the final product meets design specifications and functions well. Although mechanical durability measures like tensile or compressive strength are not included in this study, casting results have been evaluated for shape accuracy, surface quality, and pattern completeness. Further mechanical strength testing is suggested for future research.